IDA in retrospect : first two decades of the internationnal development association - World Bank. (New York, 1982)
This report was prepared by Bank staff working together with a number of outside contributors. The team was asked to undertake a frank and objective review of IDA's accomplishments and failures. The report has been reviewed by a wide range of read ers both inside and outside the Bank and from both the industrial and developing countries. Its pur pose, content, and conclusions were discussed in four seminars held in Washington, Paris, London, and New York. These outside comments and views are reflected in the text. The judgments expressed, however, do not necessarily reflect the views of the Bank's Board of Directors or the governments they represent. Reviewing IDA's history has proved a valuable experience. No institution is or could even hope to be perfect. Both IDA's shortcomings and achieve ments are evident in various parts of this report. What is most striking, however, is its record of solid achievement and its ability to learn from past mis takes. In its 20-year life, IDA has become one of the strongest, most effective bodies for promoting de velopment. It stands as a symbol of multilateral co operation and worldwide commitment to devel opment. While substantial progress has been made, the poorest countries of the world remain in des perate need of further assistance. IDA now stands in the front line of this struggle against world pov erty; it continues to need the support of both tra ditional and new donors.
Keywords: International development association (IDA)